2019
DOI: 10.3906/vet-1710-50
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and histological transformation in the gills, liver, muscles, and skin in <i>Oreochromis</i> <i>niloticus</i> induced by mercury

Abstract: Specimens of Oreochromis niloticus (One control and 3 experimental groups) were fed diets mixed with different doses of mercury (control group = free of mercury; group 1 = 500 mg/kg; group 2 = 750 mg/kg, and group 3 = 1000 mg/kg) for 60 days in order to study its accumulation and histopathological alterations in the liver, gills, skeletal muscles, and skin. The results obtained revealed that mercury accumulation was significantly (P < 0.05) high in the liver and gills compared to the muscles and skin. The orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Gill histopathological analysis revealed that the most relevant alterations found in samples from the Port of Genoa were PL and SL hyperplasia, SL hypertrophy, SL epithelial lifting, and necrosis, followed by fusion and congestion of SL with occasional granulocyte infiltration (Figs. 4 and 6); results are in accordance with literature which highlighted the presence of the same alterations in fish exposed to a contaminated environment (Al-Ghanim et al 2019;Ben Ameur et al 2015;Gad El-Hak et al 2021;Nagarjuna and Mohan 2017;Noguera et al 2019). Hyperplasia and the consequent fusion of SL, SL hypertrophy, and SL epithelial lifting are defensive changes that occurs in gill tissue to increase the distance between (Arockia Vasanthi et al 2013;Rajeshkumar et al 2015).…”
Section: Histopathological Analysessupporting
confidence: 91%
“…Gill histopathological analysis revealed that the most relevant alterations found in samples from the Port of Genoa were PL and SL hyperplasia, SL hypertrophy, SL epithelial lifting, and necrosis, followed by fusion and congestion of SL with occasional granulocyte infiltration (Figs. 4 and 6); results are in accordance with literature which highlighted the presence of the same alterations in fish exposed to a contaminated environment (Al-Ghanim et al 2019;Ben Ameur et al 2015;Gad El-Hak et al 2021;Nagarjuna and Mohan 2017;Noguera et al 2019). Hyperplasia and the consequent fusion of SL, SL hypertrophy, and SL epithelial lifting are defensive changes that occurs in gill tissue to increase the distance between (Arockia Vasanthi et al 2013;Rajeshkumar et al 2015).…”
Section: Histopathological Analysessupporting
confidence: 91%
“…Water pollution is a fast‐growing problem of 21st century worldwide (Bassem, 2020). Contamination with heavy metals (HM) is a serious problem owing to their persistence, bioaccumulation in different fish tissues, non‐degradable nature and poisonous effects (Al‐Ghanim et al, 2019; El‐Bouhy et al, 2021; Huseen & Mohammed, 2019). Heavy metals cause disastrous effects on metabolic processes, nutritional value, health and immune status of African catfish, freshwater organisms and Zebrafish (El‐Bouhy et al, 2021; Hong et al, 2020; Kim et al, 2020), also, constitute a hazard to fish consumers (Isangedighi & David, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals induced several histopathology in different important fish organs. Heavy metals contamination resulted hyperplastic and hypertrophic epithelial, chloride and mucous cells in gills, congested capillary, jointed gill lamellae, clubbing, talangiectasis in fish gill and caused respiratory difficulties (Rajeshkumar et al, 2017;Al-Ghanim et al, 2019). Liver is very much sensitive to heavy metals in comparison to other organs and several histopathological changes (necrotic and degenerated hepatocytes, cirrhosis and lysis of hepatic cells, pyknosis, and vacuoles) observed in different extent in various fish (Kawade, 2020).…”
Section: Effects Of Heavy Metals On Fishesmentioning
confidence: 99%